Witch-hunt as a Model: The Juxtaposition of the Red Scare (1948-1957) and the Salem Witch Trials (1692) - Haimoud,Siham; Boumous, Moufida (University of Ammar Theledji -Laghouat, 2020)
Western history is rich with instances of witch-hunts that vary in terms of causes and purposes, yet similar in the manner of conduct. The following dissertation aims at categorizing the Red Scare (1948-1957) as a model of witch-hunt by comparing it to the Salem Witch Trials (1692). It seeks to define the model, using Douglas Walton’s description of witch-hunting parameters. In achieving so, the dissertation follows a qualitative approach and a comparative analysis. The research paper introduces witch-hunting parameters and their sociopolitical contextualization within the first chapter. Then, it describes the Salem Witch Trials and the Red Scare in the second chapter to, ultimately, compare and analyze the two elements in the last chapter. After the analogy of the two historical events and the projection of their resemblance, the study concludes the categorization of the Red Scare as a witch-hunting model